Evidence Linking Lipid Peroxidation and Patients’ Osteoarthritis Pain - Farooqui, Salim; Nigam, Palak (Stallion Journal for Multidisciplinary Associated Research Studies, 2022)
WHO estimates that osteoarthritis (OA) affects 9.6% of men and 18% of women older than 60 years of age. Increases in life expectancy and ageing populations are expected to make OA the fourth leading cause of disability by the year 2020. Oxidative stresses are believed to function as primary degenerative mechanism in the development and progression of osteoarthritis. The exact oxidant and antioxidant status in osteoarthritis is not clear. The objectives of our study to evaluate the changes in oxidative stress marker (lipid-peroxidation) and non-enzymatic antioxidant (glutathione) in osteoarthritis patients. This study was carried out in 50 osteoarthritis and 50 normal individuals. Levels of Lipid-peroxidation marker MDA and GSH were measured by UV-VIS spectrophotometer. Increased serum MDA level is found in OA as compared to control. Significantly decreased GSH found in OA as compared to control. The result shows increased oxidative stress and decreased non-enzymatic antioxidant in osteoarthritis patients.